Nonlinear Finite Element Analysis of Space Truss - Farhan Kadhum, Ahmed (Anbar Journal of Engineering Sciences, 2012)
This paper presents an analytical investigation which includes the use of three dimensional nonlinear finite elements to model the performance of the space trusses by using (ANSYS 11.0) computer program. The numerical results show very good agreement (100%) with experimental results, while the graphical option reflects the behavior of the structure under the applied loads because of the ability of this option to simulate the real behavior of the structure under these loads. Also finite element models of the space truss simulate the lateral deflection of the top chord members especially at the corners, and the twisting of the bottom chords.